Urban governance in Asia : sub-regional and city perspectives - Islam, Nazrul (Dhaka : Centre for Urban Studies, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: Regionalism -- South Asia; South Asia -- Politics and government